Breakthrough of advanced drives for cars? Perspectives and consequences - Jørgensen, Kaj (Proceedings from the Annual Transport Conference at Aalborg University, 2002)
This paper treats the prospects for shifting to advanced drive trains in motor vehicles, particularly automobiles, and the possible environmental impacts of such shifts. The paper is partly based on a project carried out for the National Environmental Protection Agency of Denmark by Technological Institute of Denmark and Risoe National Laboratory, the report of which is yet to be published.